DEVELOPMENT OF AN AIR TRAFFIC CONTROL PHRASEOLOGY HANDBOOK TO IMPROVE AVIATION COMMUNICATION EFFECTIVENESS FOR CADETS AVIATION POLYTECHNIC OF SURABAYA - Maharani Sukma, Meita; Fatmawati; Rochmawati, Laila; A.M.G de Sousa, Delmio (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Aviation safety relies heavily on effective communication between Air Traffic Controllers (ATC) and pilots. Standardized phraseology established by the International Civil Aviation Organization (ICAO) is essential in this context. However, many cadets of the Surabaya Aviation Polytechnic still face difficulties in applying ATC phraseology consistently, which may reduce communication effectiveness. This research aimed to develop an ATC phraseology guidebook as a structured learning tool to enhance cadets’ communication skills. The study applied a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. Due to time and resource limitations, the process was conducted only up to the Develop stage. In the Define stage, needs analysis was carried out through observation and interviews. The Design stage resulted in a draft guidebook based on ICAO Doc 4444 and cadets’ needs. The Develop stage included expert validation and limited trials. Findings showed that the guidebook met feasibility standards in content, language, and presentation. Expert reviews confirmed its quality, and trial results indicated improvements in cadets’ understanding and use of ATC phraseology. Although dissemination was not completed, the product proved beneficial for supporting aviation communication effectiveness at the Surabaya Aviation Polytechnic.